SUICIDAL BEHAVIOR IN EDUCATION AND PHYSICAL EDUCATION UNDERGRADUATE STUDENTS FROM UNIVERSITY OF SAN MARCOS (LIMA-PERU) - Perales, Alberto (2014)
Previous studies carried out by Perales et al. in medical students of San Marcos University (SMU), reported global suicidal behavior’s life prevalences (L.P.) (wish to die, suicidal ideation, suicidal plan and suicidal attempt) of 30%; and specifically of suicidal attempt, 4% while in undergraduate social work students were 57.7% and 14.8% respectively. Not having data on this problem in Education and Physical Education’s undergraduate students in Peru the present study is addressed to estimate the life-prevalences of these behaviors in this student population. OBJECTIVE: To identify students of SMU’ Education and Physical Education Schools who had presented suicidal behavior and to estimatethe life prevalence (L.P.) and its associated variables in this population. METHODOLOGY: Analytic, transversal study in the students registered in 2011 in those two Schools. Previously validated instruments (Suicidal Behavior Questionnaire, Zung’s Depression and Anxiety Scales, Antisocial Behavior Indicators Scale and CAGE) were administered in group sessions in each academic year. Descriptive analysis of results and their associated variables were carried out. RESULTS: Education School, of 1027 registered students in the first semester of 2011, 490(48%), participated in the study previous acceptance of Informed Consent. The following L.P. were established: Global suicidal behavior, 52.7%(Wish to die, 48.1%; Suicidal Ideation, 28.3%; Suicidal Plan, 12.7%; and Suicidal attempt, 16.3%). In Bivariate analysis of attempted suicide significantly associations were determined with high levels of depression OR=6,05, IC 95% (3,14-11,64), p= 0,001; of anxiety OR=7,12, IC 95% (3,31-15,32), p= 0,001; homicidal thoughts, OR=3,15, IC 95% (1,71-5,83), p= 0,001; antisocial behavior indicators, OR=1,93, IC 95% (1,10-3,38) p=0,02; and suspected drinking problems (CAGE positive) OR= 3,11, IC 95% (1,31-7,37), p=0,007. Physical Education School, from 426 registered students in 2011 participated 74% (315). The L.P. found were: Global Suicidal Behavior, 31.7%(Wish to die, 28%; Suicidal Ideation, 17.5%; Suicidal Plan, 8.1%; Suicidal Attempt, 11.2%). Bivariate analysis showed suicidal attempt associated to female sex OR=2,43, IC 95% (1,18-5,01) (p=0,013); high levels of depression OR=11,52, IC 95% (3,86-34,31) (p=0,001); high levels of anxiety OR=6,99, IC 95% (2,26-21,59), (p=0,001); homicidal thoughts OR=3,57, IC 95% (1,52-8,37), (p=0,002); antisocial behavior indicators OR=3,62, IC 95% (1,71-7,67), (p=0,001) and suspected drinking problems (CAGE positive) OR=2,64, IC 95% (1,07-6,48), (p=0,029). CONCLUSIONS: The student population of Education and Physical Education Professional Schools of San Marcos University constitutes a risk groupregarding suicidal indicators associated to other mental health variables. The identified problems sufficiently important to request Peruvian University’s authorities to face its responsibility organizing the specific preventive and intervention programs.